(untitled) (CIPEEX, 2023)
In the teaching of botany, it is essential to adopt pedagogical approaches that consider the students’ daily lives and their prior knowledge about the plants present in their region. With the aim of making the study of botany more engaging and collaborative, this work proposed the creation of herbarium specimens as a methodological alternative. Herbarium specimens are samples of plants that are collected, pressed, and dehydrated, used by botanists for studies on the morphology and classification of plants. We believe that the use of herbarium specimens can enrich the teaching of botany, bringing it closer to the students’ reality. This study was conducted in the biology course at CEPI Dr. Mauá Cavalcante Sávio. Regarding the data collection method, the research was experimental, using a questionnaire for data collection. The analysis of the responses obtained in the questionnaire revealed that the majority of students found the teaching of botany more attractive and understandable when collaborative activities, such as the production of herbarium specimens, were proposed. This demonstrates that the theoretical-practical approach, which allows students to apply what they have learned in the collection and preparation of botanical samples, is highly effective. Therefore, we can conclude that the more contextualized and participatory the teaching process is, the closer we will be to providing meaningful learning.